Social and Economic Transformation - International Scan and Lessons Learnt (Global Journal of Human-Social Science, 2019)
Transformation is a necessity in many economies to address social, political and economic inequality. Addressing it normally takes the form of affirmative action. This paper reviews transformation in four selected countries, namely, Malaysia, The United States of America, Brazil and New Zealand. The paper concludes that effective transformation policies need enforcement, strong incentives and good monitoring. It also concludes that affirmative action is a process and not an event.
Keywords: transformation; affirmative action; social and economic inclusion; equality